(untitled) (SigMe, 2025)
To review the available scientific evidence on the feasibility, nutritional adequacy, and practical considerations of vegetarian and vegan diets (VDDs) during pregnancy, breastfeeding, and the first two years of life (the first 1000 days), in order to develop evidence-based technical recommendations for healthcare teams. A narrative review of the scientific literature published in recent decades was conducted, obtained from databases such as PubMed, Scopus, Web of Science, and SciELO, as well as documents from international organizations and scientific societies. Studies addressing the nutritional composition, clinical impacts, and supplementation recommendations for VDDs in this population were selected, applying predefined inclusion and exclusion criteria. A well-planned VDD can be nutritionally adequate and offer health benefits during this critical stage. However, it carries an inherent risk of specific nutrient deficiencies, with vitamin B12, iron, DHA (omega-3), and, to a lesser extent, zinc, iodine, calcium, and vitamin D being of greatest concern. Evidence indicates that strategic supplementation and consumption of fortified foods are essential to prevent deficiencies and ensure optimal development. Discrepancies in the positions of various scientific societies were identified. VVDs are feasible during the first 1000 days of life but require meticulous planning, nutritional education, and ongoing monitoring. The healthcare team plays a crucial role in counseling, focusing on mandatory vitamin B12 supplementation, adequate iron and omega-3 intake, and individualized assessment of nutritional status to ensure favorable maternal and child outcomes